Diadenosine-Polyphosphate Analogue AppCH2ppA Suppresses Seizures by Enhancing Adenosine Signaling in the Cortex. (6th October 2018) - Pons-Bennaceur, Alexandre; Tsintsadze, Vera; Bui, Thi-thien; Tsintsadze, Timur; Minlebaev, Marat; Milh, Mathieu; Scavarda, Didier; Giniatullin, Rashid; Giniatullina, Raisa; Shityakov, Sergey; Wright, Michael; Miller, Andrew D; et al.
Abstract: Epilepsy is a multifactorial disorder associated with neuronal hyperexcitability that affects more than 1% of the human population. It has long been known that adenosine can reduce seizure generation in animal models of epilepsies. However, in addition to various side effects, the instability of adenosine has precluded its use as an anticonvulsant treatment. Here we report that a stable analogue of diadenosine-tetraphosphate: AppCH2 ppA effectively suppresses spontaneous epileptiform activity in vitro and in vivo in a Tuberous Sclerosis Complex (TSC) mouse model ( Tsc1 +/− ), and in postsurgery cortical samples from TSC human patients. These effects are mediated by enhanced adenosine signaling in the cortex post local neuronal adenosine release. The released adenosine induces A1 receptor-dependent activation of potassium channels thereby reducing neuronal excitability, temporal summation, and hypersynchronicity. AppCH2 ppA does not cause any disturbances of the main vital autonomous functions of Tsc1 +/ − mice in vivo. Therefore, we propose this compound to be a potent new candidate for adenosine-related treatment strategies to suppress intractable epilepsies.